A comprehensive method for fatigue life evaluation and extension in the context of predictive maintenance for fixed ocean structures. (February 2020) - Ribeiro, Tiago; Rigueiro, Constança; Borges, Luís; Sousa, Ana
Highlights: A DNVGL-RP-C210 compatible calculation method for fatigue life evaluation encompasses Global Spectral, Simplified Probabilistic, Deterministic (with Fracture Mechanics) and Probabilistic (with Bayesian inference) Fatigue Analyses. Proposed method allows using additional information for Remaining Fatigue Life estimation, reliability and risk updating and evidence-based inspection planning. Accounting for the structural condition of one case study was able to justify a fatigue life extension of, approximately, 8.5 years. Abstract: Fixed ocean structures safe and economical usage is usually limited by its fatigue resistance. Thus, the remaining fatigue life (RFL) assessment of such structures is essential to evaluate its collapse risk, to extend its service beyond an initially established horizon and to allow evidence-based inspection planning. While numerous approaches have been proposed for RFL assessment, in the context of predictive maintenance Industry has claimed the need for a comprehensive RFL assessment method, which thoroughly defines all the required steps, allows using existing inspection results and complies with the most recent standards. Following the publication of DNVGL-RP-C210 recommendations – which establish a framework for the use of probabilistic methods for fatigue cracks inspection – we developed a detailed calculation method for fatigue life evaluation of offshore structures, taking into account the information gathered with site inspections. The proposed method spans four major steps. The first one includes Global Spectral Fatigue Analyses and is followed by one second step deemed to enhance fatigue life calculations for most fatigue-prone structural details, using a Simplified Probabilistic Fatigue Analysis. Third and fourth steps include conceiving mathematical simulation models, with Fracture Mechanics formulae, and perform Probabilistic Fatigue Analyses employing the Monte Carlo Method, respectively. The application of the method has been exemplified and validated through a real case study.